Study on Circulating Antigens in Serum of Mice With Experimental Acute Toxoplasmosis - Liu, Qi; Jiang, Wei; Chen, Yun; Zhang, Manyu; Geng, Xiaoling; Wang, Quan (Frontiers in Microbiology, 2021)
Toxoplasma gondii is a ubiquitous apicomplexan protozoan parasite that can infect all warm-blooded animals, causing toxoplasmosis. Thus, efficient diagnosis methods for acute T. gondii infection are essential for its management. Circulating antigens (CAgs) are reliable diagnostic indicators of acute infection. In this study, we established a mouse model of acute T. gondii infection and explored new potential diagnostic factors. CAgs levels peaked 60 hours after T. gondii inoculation and 31 CAgs were identified by immunoprecipitation-liquid chromatography-tandem mass spectrometry, among which RuvB-like helicase (TgRuvBL1), ribonuclease (TgRNaseH1), and ribosomal protein RPS2 (TgRPS2) were selected for prokaryotic expression. Polyclonal antibodies against these three proteins were prepared. Results from indirect enzyme-linked immunosorbent assay indicated that anti-rTgRuvBL1, anti-rTgRNase H1, and anti-rTgRPS2 mouse sera were recognized by natural excretory-secretory antigens from T. gondii tachyzoites. Moreover, immunofluorescence assays revealed that TgRuvBL1 was localized in the nucleus, while TgRNase H1 and TgRPS2 were in the apical end. Western blotting data confirmed the presence of the three proteins in the sera of the infected mice. Moreover, mice immunized with rTgRuvBL1(10.0 ± 0.30 days), TgRNaseH1 (9.67 ± 0.14 days) or rTgRPS2 (11.5 ± 0.34 days) had slightly longer lifespan when challenged with a virulent T. gondii RH strain. Altogether, these findings indicate that these three proteins can potentially be diagnostic candidates for acute toxoplasmosis. However, they hold poor protective potential against highly virulent T. gondii infection.